Conspicuous Public Goods and Leadership Selection - C. Jennings; Hein J. Roelfsema (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2004)
If voters care for the relative supply of public goods compared to otherjurisdictions, decentralized provision of public goods will be too high.Potentially, centralization internalizes the negative externalities fromthe production of these `conspicuous' public goods. However, in amodel of strategic delegation of policy making, we show that in thedecentralized policy making case the median voter may delegate to apolitician who cares less for conspicuous public goods than she doesherself. By doing so, she commits to lower public goods in the homeand in the foreign country. In contrast, with centralization the medianvoter anticipates the reduction in public goods supply by delegating toa policy maker who cares more for public goods than she does herself.This last effect mitigates the expected benefits of centralization.
Keywords: 330; Conspicuous goods; strategic delegation; policy centralization